Rumbo a DSpace 7 - Mennielli, Michele (2018)
DuraSpace is not for profit organization that provides leadership and innovation for open technologiesWe work to ensure that current and future generations have durable andpersistent accessto our collective digital heritage Our communityis part of an interconnected, worldwide, scholarly ecosystem. Version 7.0 goals: - Single, Angular UI (new), - Fully-featured REST API, (new), - Configurable Entities (new), - Align w/ NGR recommendations, - Existing, core Java backend (DB, Solr, Assetstore).